2006
DOI: 10.1590/s1676-06032006000200007
|View full text |Cite
|
Sign up to set email alerts
|

Pequenos mamíferos não-voadores da Reserva Florestal do Morro Grande: distribuição das espécies e da diversidade em uma área de Mata Atlântica

Abstract: Non-volant small mammals, the most diverse ecological group of mammals in Neotropical forests, play an important role in forest dynamics and are good indicators of both local and landscape alterations. However, little is known about species and diversity distribution and only a few of the largest Atlantic Forest remnants have been adequately sampled. Based on a survey we carried out in the Morro Grande Forest Reserve, São Paulo State, and on other 20 Atlantic forest inventories, this study aims at (1) describi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
28

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 53 publications
2
46
0
28
Order By: Relevance
“…In addition, the sample area is not protected under a conservation unit. Pardini & Umetsu (2006) provided a summary of 20 surveys of small mammals in Atlantic Forest fragments representing an area greater than 700 ha; however, only two of these studies (Bonvicino et al 1997 andPardini &Umetsu 2006) found richness equal to or greater than that reported here. In a study near the Paranapiacaba ecological continuum, Leiner & Silva (2012) caught 20 species of small nonvolant mammals in one of the largest regions of Atlantic forest (due to the presence of four conservation units).…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…In addition, the sample area is not protected under a conservation unit. Pardini & Umetsu (2006) provided a summary of 20 surveys of small mammals in Atlantic Forest fragments representing an area greater than 700 ha; however, only two of these studies (Bonvicino et al 1997 andPardini &Umetsu 2006) found richness equal to or greater than that reported here. In a study near the Paranapiacaba ecological continuum, Leiner & Silva (2012) caught 20 species of small nonvolant mammals in one of the largest regions of Atlantic forest (due to the presence of four conservation units).…”
Section: Discussionmentioning
confidence: 56%
“…Despite the high richness found in the area, the fragment sampled is small compared to other sampled areas in the biome (Galiano et al 2013, Pardini & Umetsu 2006, Geise et al 2004, Grelle 2003. In addition, the sample area is not protected under a conservation unit.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations